In Vitro and In Vivo Antiviral Activity of Nylidrin by Targeting the Hemagglutinin 2-Mediated Membrane Fusion of Influenza A Virus - Jang, Yejin (Viruses, 2020)
Influenza A virus, one of the major human respiratory pathogens, is responsible for annual seasonal endemics and unpredictable periodic pandemics. Despite the clinical availability of vaccines and antivirals, the antigenic diversity and drug resistance of this virus makes it a persistent threat to public health, underlying the need for the development of novel antivirals. In a cell culture-based high-throughput screen, a β2-adrenergic receptor agonist, nylidrin, was identified as an antiviral compound against influenza A virus. The molecule was effective against multiple isolates of subtype H1N1, but had limited activity against subtype H3N2, depending on the strain. By examining the antiviral activity of its chemical analogues, we found that ifenprodil and clenbuterol also had reliable inhibitory effects against A/H1N1 strains. Field-based pharmacophore modeling with comparisons of active and inactive compounds revealed the importance of positive and negative electrostatic patterns of phenyl aminoethanol derivatives. Time-of-addition experiments and visualization of the intracellular localization of nucleoprotein NP demonstrated that an early step of the virus life cycle was suppressed by nylidrin. Ultimately, we discovered that nylidrin targets hemagglutinin 2 (HA2)-mediated membrane fusion by blocking conformational change of HA at acidic pH. In a mouse model, preincubation of a mouse-adapted influenza A virus (H1N1) with nylidrin completely blocked intranasal viral infection. The present study suggests that nylidrin could provide a core chemical skeleton for the development of a direct-acting inhibitor of influenza A virus entry.